2022
DOI: 10.9734/ijecc/2022/v12i930736
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-term Fertilization and Manuring on Soil Enzyme Activity in Rice-rice Cropping System in Semi-arid Southern India

Abstract: Nutrient management practices have huge influence on soil biological health. The present study was conducted during kharif-2021 in the on-going AICRP on LTFE after 21 years of continuous application of fertilizers and manures to estimate the enzymatic activities i.e., urease and dehydrogenase activity at different growth stages of rice crop. In all the treatments, enzymes exhibited higher activity at flowering stage and thereafter the activity was decreased towards harvesting stage of the rice crop. Among all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…This was not consistent with the study by Li et al that showed that soil enzyme activities decreased first and then increased under the condition of muskmelon planting under aerated irrigation [37]. The activity was also affected by the soil nutrients, seasons, management practices and other conditions [38,39]. The soil urease activity of soil treated with oxygen improved significantly during the fruit expansion stage and maturation stage, and the soil urease activity of soil treated with water was also positively affected during the flowering and fruit-setting stage and fruit expansion stage, but was opposite in the maturation stage.…”
Section: Effects On Soil Enzyme Activity and Microbial Biomass In The...contrasting
confidence: 82%
“…This was not consistent with the study by Li et al that showed that soil enzyme activities decreased first and then increased under the condition of muskmelon planting under aerated irrigation [37]. The activity was also affected by the soil nutrients, seasons, management practices and other conditions [38,39]. The soil urease activity of soil treated with oxygen improved significantly during the fruit expansion stage and maturation stage, and the soil urease activity of soil treated with water was also positively affected during the flowering and fruit-setting stage and fruit expansion stage, but was opposite in the maturation stage.…”
Section: Effects On Soil Enzyme Activity and Microbial Biomass In The...contrasting
confidence: 82%
“…Continuous application of FYM has been found to increase the dehydrogenase activity at various growth stages of rice under rice-rice cropping systems in semi-arid region of South India [ 29 ]. Integrated nutrient management (INM) with the inclusion of organic manures like poultry manure, urban compost, maize residue, green manures, FYM, and press mud also resulted in higher alkaline phosphatase, arylsulfatase, and dehydrogenase activities under different cropping systems [ 5 , [30] , [31] , [32] , [33] ].…”
Section: Introductionmentioning
confidence: 99%